Nonvolatile Random Access Memory and Energy Storage Based on Antiferroelectric Like Hysteresis in ZrO2. (7th September 2016) - Pešić, Milan; Hoffmann, Michael; Richter, Claudia; Mikolajick, Thomas; Schroeder, Uwe
Abstract : To date antiferroelectrics have not been considered as nonvolatile memory elements because a removal of the external field causes a depolarization, resulting in a loss of the stored information. In comparison to ferroelectrics, antiferroelectrics are known for their enhanced fatigue resistance. Therefore, the main scope of this study is the development of a new memory device concept that would enable the usage of antiferroelectrics as a nonvolatile material with improved wake‐up and enhanced endurance properties. Recent studies have shown antiferroelectric behavior in ZrO2, a material that is widely used in semiconductor industry, especially in dynamic random access memories. The basis of the new concept is the antiferroelectric hysteresis combined with the use of different workfunction electrodes that induce an internal bias field. Utilizing this approach, the field cycling endurance is drastically improved. Combining a comprehensive material study and electrical trap spectroscopy together with Landau–Ginzburg–Devonshire formalism, a proof of concept for a novel antiferroelectric random access memory is presented. For implementing a nonvolatile random access memory, the capacitors have to be realized in a 3D integrated version. These 3D integrated ZrO2 capacitors can be used as energy storage devices as well, showing record high energy storage density and very high energy efficiency values. Abstract : A new paradigm for nonvolatile antiferroelectric memories is presented. By introduction of built‐in bias, one side of antiferroelectric hysteresis branch is centered, enabling nonvolatile data storage. Through this, significantly improved field cycling endurance is demonstrated for antiferroelectric ZrO2 films, compared to HfO2 ferroelectrics.